Ketangguhan Keluarga Menghadapi Pandemi COVID 19: Perspektif Psikologi dan Islam - Djamal, Nani Nuranisah; Hidayat, Ila Nurlaila; Tahrir, Tahrir; Jaenudin, Ujam (Psikologika: Jurnal Pemikiran dan Penelitian Psikologi, 2022)
Often stressful or traumatic events have different effects on different individuals in the family. However, family resilience refers to the ability to maintain the family functions, including to provide supports for all family members. This study aims to explain the relevance of the meaning contained in the concept of family resilience through Islamic values, associated with its implementation in the context of the COVID-19 pandemic. The research method was Islamic Psychology development. The results found that there are a number of verses of the Quran and Hadith that have relevant meaning to the six dimensions of family resilience according to Oh dan Chang (2014). The dimension of collective confidence is relevant to the concepts of patience, self-confidence, firm conviction and being not desperate. Dimension of interconnectedness is relevant to the command to protect oneself and the family, to unite (not being divorced) and to avoid prejudice. The dimension of positive life view is relevant to have the positive thinking (husnudzan) towards the decree of Allah, to believe that after difficulties there will be ease, and to believe that each self is only burdened according to the limits of his ability. The dimension of resourcefulness is relevant to the command to make effort on the things we do and to have th hard work. The dimension of open communication patterns is relevant to have love and affection, to have dialogue with others, and to remind each other. Whereas the dimension of collaborative problem solving is relevant to help each other, to compete in good deeds, and to prioritize others.